2017
DOI: 10.1111/hae.13356
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of FXI deficiency in a Spanish town caused by 11 different mutations and the first duplication of F11: Results from the Yecla study

Abstract: Our population-cohort study supplies new evidences that FXI deficiency in Caucasians is more common than previously thought and confirmed the wide underlying genetic heterogeneity, caused by both recurrent and sporadic mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Our study is limited by the small sample size from a single institution. Even with recent estimates of a heterozygous frequency as high as one in 300, a large, multicenter study would still be required to determine the true prevalence of children with hemophilia C who have a normal aPTT without factor replacement . Also, as the combined effect of all intrinsic factor activities can affect the aPTT, our study would have been further strengthened if intrinsic factor activities were available for all subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study is limited by the small sample size from a single institution. Even with recent estimates of a heterozygous frequency as high as one in 300, a large, multicenter study would still be required to determine the true prevalence of children with hemophilia C who have a normal aPTT without factor replacement . Also, as the combined effect of all intrinsic factor activities can affect the aPTT, our study would have been further strengthened if intrinsic factor activities were available for all subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A more contemporary study of 60,000 inhabitants of a south‐eastern Spanish town found 216 subjects with factor XI deficiency. Nearly one‐third of the subjects had a nearly normal aPTT . Again, it is unclear how many of these subjects were children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This population-based cohort study supplies new evidence that FXI deficiency in Caucasians is more common than previously thought and confirmed the wide underlying genetic heterogeneity. 75…”
Section: Hts As a Clinical Epidemiological Toolmentioning
confidence: 99%
“…Although it was first described prevalent in exclusively etnias (Ashkenazy or Iraqi-Jewish), it seems to be misdiagnosed and not so exclusive, with a potential high prevalence at least in heterozygosis, also in Europe. 1 Moreover, acquired deficiency can occur with the presence of inhibitors or antibodies such as antiphospholipid as β2-glycoprotein I. 2 Whether or not COVID-19 contributing to the appearance of antiphospholipid antibodies, is still unclear and requires further studies.…”
mentioning
confidence: 99%